2020
DOI: 10.1126/sciadv.aba3442
|View full text |Cite
|
Sign up to set email alerts
|

Controllable freezing of the nuclear spin bath in a single-atom spin qubit

Abstract: The quantum coherence and gate fidelity of electron spin qubits in semiconductors are often limited by nuclear spin fluctuations. Enrichment of spin-zero isotopes in silicon markedly improves the dephasing time T2* Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…Future work will focus on integrating this method within multi-qubit systems [5,54]. We expect it will improve the fidelity in preparing highly entangled quantum states, and enable sufficient state preparation fidelity to implement quantum error correction codes [1,2] at a fault-tolerant level.…”
Section: Discussionmentioning
confidence: 99%
“…Future work will focus on integrating this method within multi-qubit systems [5,54]. We expect it will improve the fidelity in preparing highly entangled quantum states, and enable sufficient state preparation fidelity to implement quantum error correction codes [1,2] at a fault-tolerant level.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Earlier studies showed that similarly low values of trap densities are retained after ion implantation, followed by a hightemperature rapid thermal anneal and a forming gas anneal. [47] The high quality of postimplantation oxides is further corroborated by the robust charge and spin properties of qubit devices based on ionimplanted donors as studied in the past decade [10][11][12][13][14][15][16]26,48]…”
Section: Single-ion Implant Detectorsmentioning
confidence: 99%
“…[12] Singlequbit error rates are in the 0.01-0.03% range, [13,14] thus addressing requirement (ii) at the 1qubit level. Conditional twoqubit operations between exchangecoupled donors elec trons have been recently demonstrated, [15] as well as universal twoqubit logic gates for donor nuclear spins with sub1% error rates. [16] In this work, we demonstrate that the industrystandard ion implantation method can be extended to the deterministic implantation of individual dopant atoms with such high confi dence to address requirement (iii) for the fabrication of donor qubit arrays with a low density of faulty or absent qubits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in order to compose multi-qubit unitaries from this universal set, one must know how to do these one-and two-qubit gates without disturbing the other qubits. This is not a trivial task when the interaction between qubits cannot easily be turned off, as is the case for silicon spin qubits in some dot [16][17][18][19] and donor [20,21] systems.…”
Section: Introductionmentioning
confidence: 99%